2010
DOI: 10.2202/1553-3840.1290
|View full text |Cite
|
Sign up to set email alerts
|

Thai Yoga as an Appropriate Alternative Physical Activity for Older Adults

Abstract: Thai Yoga (TY), has been recommended by the Public Health Ministry of Thailand for keeping people fit. There is little known about the physiological demand it places on those practicing it. Therefore, the purpose of this study is to determine i) the exercise intensity of TY indicating by both absolute intensity (i.e. MET) and relative intensity (i.e. percentage of maximal oxygen consumption (VO2,max) and heart rate (HRmax)) and ii) the impact it has on the cardiovascular system and energy expenditure. Fourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Of the total studies, 35 studies were published from India, 70,71,85 –117 15 from the United States, 118 –132 2 from the United Kingdom, 133,134 and 1 each from Mexico, 135 New Zealand, 136 Thailand, 137 Brazil, 138 Japan, 139 and Sweden. 140 Most studies reported assessing direct measurement of respired gases for measuring oxygen consumption using indirect calorimetry techniques, whether through open circuit, closed circuit, bag system, or respiratory chamber method.…”
Section: Resultsmentioning
confidence: 99%
“…Of the total studies, 35 studies were published from India, 70,71,85 –117 15 from the United States, 118 –132 2 from the United Kingdom, 133,134 and 1 each from Mexico, 135 New Zealand, 136 Thailand, 137 Brazil, 138 Japan, 139 and Sweden. 140 Most studies reported assessing direct measurement of respired gases for measuring oxygen consumption using indirect calorimetry techniques, whether through open circuit, closed circuit, bag system, or respiratory chamber method.…”
Section: Resultsmentioning
confidence: 99%
“…Thai yoga or Ruesri Dat Ton is an alternative exercise option of a traditional Thai activity that could be used to improve physical performance in elderly Thai [10]. This study, utilized modified Thai Yoga postures to safely promote this traditional Thai activity in obese older women.…”
Section: Discussionmentioning
confidence: 99%
“…Buranruk [10], examined the metabolic intensity of Thai Yoga exercise by studying 14 older adults with a BMI of > 25.75 kg/m² (obese). They performed 30 min of Thai Yoga that including 8 sitting postures, 4 standing postures and 3 lying postures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TY may also have benefits in terms of stress management stemming from the meditation, relaxation and message aspects of the system. If individuals perform TY for longer duration especially standing position, they may gain benefits including reduction in cardiovascular mortality, reduction of symptoms, improvement in exercise tolerance and function capacity, and improvement in psychological well-being and quality of life [32].…”
Section: Thai Yoga (Ty)mentioning
confidence: 99%